Perencanaan Administrasi Sekolah sebagai Upaya Pengembangan Kinerja Tenaga Kependidikan di MTsN 4 Aceh Besar - Yusra Jamali; Zakky Mubarrak; Vira Asfarina Yusra (LaKaspia, 2025)
School administration management systems and models are solely designed for the development of school resource performance, including educational personnel. The preparation and implementation of activities are carried out sporadically and simultaneously so that all available facilities can be used effectively to improve school administrative services. This study aims to determine the readiness of school administration planning in developing the performance of educational personnel at MTsN 4 Aceh Besar and to identify the strategies prepared to overcome obstacles and challenges in school administration planning in developing the performance of educational personnel at MTsN 4 Aceh Besar. The research uses a descriptive qualitative approach, with data collection techniques carried out through observation, interviews, and documentation analysis. The data sources consist of the school principal, school administrative officials, and users of educational services. The results show that school administrative planning is prepared through a system of meetings at the beginning of the year, preparing work references and guidelines, and conducting evaluations at the beginning and end of each year. Meanwhile, strategies to minimise obstacles are carried out by preparing training schemes for existing resources, improving the functionality of available facilities, and providing adequate funds for the performance of educational personnel at the school